Combined Endoscopic Stent-In-Stent Placement by Lumen-Apposing Metal Stents Through Self-Expanding Metal Stents for Simultaneous Malignant Biliary and Duodenal Obstruction. Issue 11 (23rd November 2021) - Metelli, Flavio; Pezzoli, Alessandro; Fabbri, Carlo; Pizzo, Elena; Arena, Rosario; Cifalà, Viviana; Simone, Loredana; Solimando, Riccardo; Merighi, Alberto
ABSTRACT: The palliation of simultaneous biliary and duodenal obstruction in patients with advanced pancreatic cancer is a clinically and technically challenging scenario. Endoscopic procedures are a valid alternative to surgical or percutaneous transhepatic biliary drainage. The availability of self-expanding metal stents (SEMSs) and lumen-apposing metal stents (LAMS) have expanded therapeutic options. We describe a case in which biliary and duodenal obstructions were treated successfully with the combined use of SEMS and LAMS devices. Endoscopic ultrasound-guided biliary drainage with the use of new LAMS and a duodenal SEMS can be a valid option in expert hands as a palliative and minimally invasive treatment for gastric outlet and biliary obstruction.